Tumour necrosis factor inhibitor exposure and radiographic outcomes in Veterans with rheumatoid arthritis: a longitudinal cohort study. Issue 1 (28th May 2019) - Cannon, Grant W; Erickson, Alan R; Teng, Chia-Chen; Huynh, Tina; Austin, Sharon; Wade, Sally W; Stolshek, Bradley S; Collier, David H; Mutebi, Alex; Sauer, Brian C
Abstract: Objectives: The aim was to estimate the impact of TNF inhibitor (TNFi) exposure on radiographic disease progression in US Veterans with RA during the first year after initiating therapy. Methods: This historical longitudinal cohort design used clinical and claims data to evaluate radiographic progression after initiation of TNFi. US Veterans with RA initiating TNFi treatment (index date), ≥ 6 months pre-index and ≥ 12 months post-index VA enrolment/activity, and initial (6 months pre-index to 30 days post-index) and follow-up (10–18 months post-index) bilateral hand radiographs were eligible. The cumulative TNFi exposure and change in modified Sharp score (MSS) between initial and follow-up radiographs were calculated. The percentage of patients with clinically meaningful change in MSS (≥ 5) for each month of exposure was assessed using a longitudinal marginal structural model with inverse probability of treatment weights. Mean values and CIs were generated using 1000 bootstrapped samples. Results: For 246 eligible patients, the mean (s .d .) age was 58 (11) years; 81% were male. The mean (s .d .) initial MSS was 19.6 (33.4) (range 0–214). The mean change (s .d .) in MSS was 0.3 (3.6) (median 0, range −19 to 22). Patients with the greatest exposure had the least radiographic progression for both crude and adjusted model analyses. Adjusted rates of MSS change ≥ 5 points (95% CI) were 10.6% (9.8%, 11.4%) for patients with 3 months of exposure compared with 5.4% (5.1%, 5.7%) for patients with 12 months of exposure. Conclusion: One-year changes in radiographic progression were small. Patients with the greatest cumulative TNFi exposure experienced the least progression.